2009
DOI: 10.2174/1871520610909040415
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of P-gp Inhibitors

Abstract: During the last decades multidrug resistance (MDR) emerged as main problem in the anti-cancer therapy with cytostatically active agents. Classical as well as recently developed cytostatics develop the phenomenon of loosing activity in former drug-sensitive cells. Although MDR is a multifactorial process, the main obstacle is the expression of multidrug-efflux pumps that lowers the intracellular drug levels. P-glycoprotein (P-gp) is the longest identified efflux pump. As the attempt to overcome MDR by the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…A critical defense of tumor cells against chemotherapy is the ability of several well-studied plasma membrane pumps to export anti-cancer drugs taken up by the cells, thus reducing the intracellular residence time of the agents (Baumert & Hilgeroth, 2009;Sharom, 2008). Rebbaa et al (2008) have shown that tetrac increases the intracellular residence time of doxorubicin in chemoresistant human breast MCF-7 cells, thus restoring chemosensitivity to this agent.…”
Section: Thyroid Hormone and Cancer Cell Chemosensitivitymentioning
confidence: 99%
“…A critical defense of tumor cells against chemotherapy is the ability of several well-studied plasma membrane pumps to export anti-cancer drugs taken up by the cells, thus reducing the intracellular residence time of the agents (Baumert & Hilgeroth, 2009;Sharom, 2008). Rebbaa et al (2008) have shown that tetrac increases the intracellular residence time of doxorubicin in chemoresistant human breast MCF-7 cells, thus restoring chemosensitivity to this agent.…”
Section: Thyroid Hormone and Cancer Cell Chemosensitivitymentioning
confidence: 99%
“…consistent with this, loVo-pcIApIn1 cells showed increased releasing index, whereas LoVo/Adr-pSiCIAPIN1 cells decreased. To confirm that the differences in drug accumulation were due to p-gp activity, we performed similar assay in loVo-pcIApIn1 cells in the presence of verapamil, an inhibitor of p-gp activity (15). As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…loVo cells were seeded in 6-well plates and grown in maintenance medium. the pgl3-MDr-1 vector (promoter of MDr-1, -136 to +10) and the control vector were established previously (15). Briefly, cells were co-transfected with indicated amounts of pcDnA3.1/ cIApIn1 plasmids (0.3, 0.6 and 0.9 µg), pgl3-MDr-1 and prl-tK vector using the Fugene transfection regent (roche, Indianapolis, In, UsA).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of these pumps in tumor cells gives them the ability to evade the treatment by drugs such as cisplatin, fluoropyrimidines, doxorubicin and etoposide in different types of cancer (Jedlitschky et al, 1996;Kool et al, 1997;Xu et al, 2010;Zelcer et al, 2001). Therefore, the use of chemomodulators to inhibit efflux transport has been tested in an attempt to overcome this resistance (Baumert and Hilgeroth, 2009;. In this way, a recent study has demonstrated that indomethacin and SC236 inhibit Pgp and MRP1 expression and thus enhance the cytotoxicity of doxorubicin in human hepatocellular carcinoma cells (Ye et al, 2011).…”
Section: Drug Transportmentioning
confidence: 99%